Development and characterization of polyester/ramie fiber hybrid composites reinforced with crystalline nanocellulose extracted from durian peel waste - Henny Pratiwi; Kusmono; Muhammad Waziz Wildan (Journal of Materials Research and Technology)
Using natural fibers and natural fillers as composite reinforcing materials has received great attention due to its potential to improve mechanical, thermal, biodegradable, and tribological properties while promoting sustainability. The present paper investigated unidirectional ramie fiber-reinforced polyester composites treated with alkali and oxalic acid and incorporating cellulose nanocrystals (CNCs) to assess their performance. Hybrid composites were created by adding 0.5, 0.75, and 1 wt% CNCs to polyester/ramie composites using the vacuum infusion technique. Mechanical and thermal tests and morphological examination were carried out to assess the influence of CNCs content on the composite properties. The results demonstrated that the presence of CNCs notably improved the mechanical performances of the polyester/ramie fiber composites. The optimal CNCs loading was attained at 0.75 wt% where the tensile strength, tensile modulus, flexural strength, flexural modulus, interlaminar shear strength, and impact strength of the polyester/ramie fiber composites were enhanced by 27.23, 33.12, 39.41, 84.56, 31.91, and 49.53%, respectively. This was confirmed by FE-SEM observations of hybrid composites, which showed good interfacial adhesion between ramie fiber and polyester/CNCs matrix. The addition of CNCs was found not to affect the thermal characteristics of the hybrid composites. Overall, polyester/ramie fiber hybrid composites containing CNCs provided great potential for structural applications.